Expression analysis of defense related genes in wheat and maize against Bipolaris sorokiniana. (August 2018) - Manghwar, Hakim; Hussain, Amjad; Ullah, Abid; Gul, Summia; Shaban, Muhammad; Khan, Aamir Hamid; Ali, Musrat; Sani, Syed Gul Abbas Shah; Chaudhary, Hassan Javed; Munis, Muhammad Farooq Hussain
Abstract: Wheat ( Triticum aestivum L.) and maize ( Zea mays L.) are important cereal crops grown worldwide. In Pakistan, various varieties of wheat and maize are grown and a number of biotic and abiotic factors influence its production. These are mainly used as a food source and raw material for animal feed. Bipolaris sorokiniana is a hemibiotrophic phytopathogenic fungus that affects various grass species and causes number of diseases on small grains. An investigation was undertaken to evaluate the comparative expression of pathogenesis-related protein genes in wheat and maize under B. sorokiniana stress. After stress, these crops showed disease resistance by improving biochemical parameters like proline, protein, sugar and chlorophyll content. Morpho-physiological parameters including shoot length, root length, relative water content and fresh as well as dry weight were affected by fungal stress. Expression analysis of PR-proteins in stressed plants of wheat confirmed their role in plant defence. PR-1, Thaumatin-like protein (TLP), and β 1, 3 glucanase were highly expressed under stress in wheat variety (RWP13), it suggests the role of these genes in the prescribed variety. These genes did not show their expression in susceptible wheat variety (SWG13). Zm PR-5 and Zm 1, 3 β-glucanase were highly expressed in maize variety (RMN27) after stress which suggests their role in defence mechanism of this variety. While on the other hand, no significant expression of these genes was observed in susceptible maize variety (SMIG). In future, these genes can be over-expressed in transgenic plants to make them resistant against a number of biotic and abiotic factors. Highlights: Plants are being challenged by number of biotic and abiotic stresses. Plants protect themselves by activating different mechanisms. Wheat and maize crops are seriously affected by biotic and abiotic stresses at world level. B. sorokiniana a hemibiotrophic phytopathogenic fungus that infects various kinds of crops at world level. The pathogenesis-related (PR) protein genes protect these crops against biotic and abiotic stresses.